Sense and sensibility - Austen, Jane (Wordsworth Classics London [England], 2011)
A comedy of manners in which the sisters Elinor and Marianne represent these two qualities. Elinor's character is one of Augustan detachment, while Marianne, a fervent disciple of the Romantic Age, learns to curb her passionate nature in the interests of survival